(untitled) (International Journal of Engineering and Computer Science, 2019)
This paper is aimed at designing a dynamic web – based Contract Bidding Information System that will be used to register details online to enable bidding for advertised contracts. It was motivated by the growing recognition of the need to modify bidding operation previously done manually. The Structured System Analysis and Design Methodology (SSADM) was used to develop a contract bidding system. A web – based application will be developed to enable bidders register and submit their biddings online.